2023
DOI: 10.1113/jp285271
|View full text |Cite
|
Sign up to set email alerts
|

An individual's skin stiffness predicts their tactile discrimination of compliance

Bingxu Li,
Gregory J. Gerling

Abstract: Individual differences in tactile acuity have been correlated with age, gender and finger size, whereas the role of the skin's stiffness has been underexplored. Using an approach to image the 3‐D deformation of the skin surface during contact with transparent elastic objects, we evaluate a cohort of 40 young participants, who present a diverse range of finger size, skin stiffness and fingerprint ridge breadth. The results indicate that skin stiffness generally correlates with finger size, although individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that gender indeed matters in terms of the density of mechanoreceptors [46], tactile discrimination and acuity [47,48], etc. Generally speaking, young females tend to show better tactile perception.…”
Section: Gender Effectmentioning
confidence: 98%
“…Previous studies have shown that gender indeed matters in terms of the density of mechanoreceptors [46], tactile discrimination and acuity [47,48], etc. Generally speaking, young females tend to show better tactile perception.…”
Section: Gender Effectmentioning
confidence: 98%
“…Specifically, skin on the foot sole is thicker (Chao et al, 2011), harder, and more variable, than palmar skin (Falanga and Bucalo, 1993;Strzalkowski et al, 2015). It has been shown that skin stiffness directly affects discrimination accuracy for the softness of different materials (Li and Gerling, 2023), with greater stiffness leading to poorer compliance discrimination. This suggests that perception at the foot may be poorer compared to the hand due to differences in skin mechanics.…”
Section: Introductionmentioning
confidence: 99%